Surveys, Big Data, and Experiments : How Can We Best Learn about LGBTI Development Outcomes? - Koehler, Dominik (World Bank, Washington, DC, 2017)
There is little rigorous quantitative data about the lives of lesbian, gay, bisexual, transgender, and intersex (LGBTI) people in developing countries. This makes the development of policy to improve the welfare of lesbian, gay, bisexual, transgender, and intersex people difficult, and it also makes it difficult to know whether lesbian, gay, bisexual, transgender, and intersex–focused policies and programs are working. Filling this data gap is necessary to understand the development outcomes for lesbian, gay, bisexual, transgender, and intersex people. Quantitative data practices exist that can be drawn on to fill the gap, including household surveys, experiments, and big data analysis. Summarizing existing experience, this paper provides guidance on how to study development outcomes for lesbian, gay, bisexual, transgender, and intersex people, by: paying attention to the different ways to define sexual orientation, gender identity and expression, and sex characteristics; and collecting samples that allow conclusions to be drawn with the broader lesbian, gay, bisexual, transgender, and intersex community, as well as the general population.